Sustainable Influencer Marketing: Leveraging AI and AR Tools to Promote Green Lifestyles - Lina Tio; Salamiah Muhd Kulal; Dorris Yadewani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study examines the integration of artificial intelligence (AI) and augmented reality (AR) technologies in sustainable influencer marketing campaigns, using Malaysia Palm Oil Board (MPOB) as a case study. The research explores how MPOB leverages digital tools to reshape public perception of palm oil sustainability through strategic influencer partnerships and immersive technologies. Based on desk research utilizing publicly available secondary data, this study addresses the gap in understanding how government-linked organizations employ AI-driven influencer selection and AR-enhanced content to promote environmental stewardship. The findings reveal that AI-powered analytics enable more precise targeting of eco-conscious audiences, while AR tools provide immersive experiences that enhance message credibility and engagement. This research contributes to the growing body of literature on sustainable marketing communications and provides practical insights for organizations seeking to balance commercial interests with environmental advocacy